Analisis pelayanan publik dalam implementasi Program Keluarga Harapan (PKH) di Kelurahan Tatura Selatan, Kota Palu - Nurziah, Nurziah; Ariani, Nora; Annisa, Chikal (Nur Science Institute, 2025)
This study aims to evaluate the quality of public services in Tatura Selatan Sub-district, Palu City, with a specific focus on the distribution mechanism of the Family Hope Program (PKH). A qualitative approach was employed to analyze four main dimensions: service effectiveness, community satisfaction, response speed, and bureaucratic communication. The findings indicate that public service delivery at the sub-district level is relatively effective and meets most of the beneficiaries' needs. However, response speed and communication still require improvement, particularly in information dissemination and administrative simplification. Academically, this study contributes to the existing literature on public service implementation at the local administrative level by emphasizing the integration of effectiveness, responsiveness, and communication within social assistance programs. The novelty of this research lies in its micro-level approach that links bureaucratic performance dynamics with beneficiaries' perceptions, offering a new perspective on how social service quality can be enhanced through the synergy of internal governance and public communication strategies. The findings provide a foundation for recommendations to improve effectiveness, satisfaction, responsiveness, and communication in social program implementation, ensuring greater transparency, adaptability, and accountability.